Synthesis and coordination chemistry of hexadentate picolinic acid based bispidine ligands - Comba, Peter; Grimm, Laura; Orvig, Chris; Rück, Katharina; Wadepohl, Hubert (Inorganic chemistry, 2016)
The synthesis and CuII, NiII, ZnII, CoII, and GaIII coordination chemistry of the two isomeric hexadentate N5O ligands 6-[[9-hydroxy-1,5-bis(methoxycarbonyl)-7-methyl-6,8-bis(pyridin-2-yl)-3,7-diazabicyclo[3.3.1]nonan-3-yl]methyl]picolinic acid (Hbispa1a) and 6-[[9-hydroxy-1,5-bis(methoxycarbonyl)-7-methyl-2,4-bis(pyridin-2-yl)-3,7-diazabicyclo[3.3.1]nonan-3-yl]methyl]picolinic acid (Hbispa1b), picolinic acid-appended bispidines, are described. The two ligands are highly preorganized for octahedral coordination geometries and are particularly well suited for tetragonal symmetries, i.e., for Jahn-Teller labile ground states. This is confirmed by all data presented: solid-state structures, solution spectroscopy, electrochemistry, and CuII complex stabilities. Differences in the preorganization of the two isomers for the Jahn-Teller labile CuII centers are thoroughly analyzed on the basis of the crystal structures and an angular-overlap-model-based ligand-field analysis.
Gesehen am 04.05.2020